Health-Related Quality of Life Is Severely Affected in Primary Orthostatic Tremor - Maugest, Lucie; McGovern, Eavan M.; Mazalovic, Katia; Doulazmi, Mohamed; Apartis, Emmanuelle; Anheim, Mathieu; Bourdain, Frédéric; Benchetrit, Eve; Czernecki, Virginie; Broussolle, Emmanuel; Bonnet, Cecilia; Falissard, Bruno; et al. (Frontiers in Neurology, 2018)
Background Primary orthostatic tremor (POT) is a movement disorder characterized by unsteadiness upon standing still due to a tremor affecting the legs. It is a gradually progressive condition with limited treatment options. Impairments in health-related quality of life (HQol) seem to far exceed the physical disability associated with the condition. Methods A multi-center, mixed methodology study was undertaken to investigate 40 consecutive patients presenting with POT to four movement disorder centers in France. HQoL was investigated using eight quantitative scales and a qualitative study which employed semi-structured interviews. Qualitative data was analysed with a combination of grounded theory approach and thematic analysis. Results Our results confirm that HQoL in POT is severely affected. Fear of falling was identified as the main predictor of HQoL. The qualitative arm of our study explored our initial results in greater depth and uncovered themes not identified by the quantitative approach. Conclusion Our results illustrate the huge potential of mixed-methodology in identifying issues influencing HQoL in POT. Our work paves the way for enhanced patient care and improved HQoL in POT, and is paradigmatic of this modern approach for investigating HQoL issues in chronic neurological disorders.